2004
DOI: 10.1124/mol.104.006056
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal Degradation of Human CYP1B1: Effect of the Asn453Ser Polymorphism on the Post-Translational Regulation of CYP1B1 Expression

Abstract: Allelic variations in CYP1B1 are reported to modulate the incidence of several types of cancer. To provide a mechanistic basis for this association, we investigated the impact of nonsilent allelic changes on the intracellular levels and post-translational regulation of CYP1B1 protein. When transiently expressed in COS-1 cells, either in the presence or absence of recombinant cytochrome P450 reductase, the cellular level of the CYP1B1.4 allelic variant (containing a Ser at the amino acid position 453; Ser453) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 42 publications
4
64
2
1
Order By: Relevance
“…However, other functionally important CYP1B1 variants, including CYP1B1.3 and CYP1B1.4, were not evaluated, and other studies have shown that both CYP1B1.3 and CYP1B1.4 are important in determining catalytic efficiency and the protein processing of CYP1B1 in both COS-1 and other cellular expression systems. Recently, others have shown that the CYP1B1.4 variant increases the degradation efficiency of CYP1B1 by proteases and the proteasome in COS-1 cells, although the precise mechanism to explain these results remains to be elucidated (50,113). When expressed by bacteria in an ex vivo assay, the CYP1B1.3 variant alone was found have the lowest catalytically efficiency toward estrogen 4-hydroxylation reactions and the lowest ratio of 4-OHE 2 :2-OHE 2 formation.…”
Section: Polymorphismsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, other functionally important CYP1B1 variants, including CYP1B1.3 and CYP1B1.4, were not evaluated, and other studies have shown that both CYP1B1.3 and CYP1B1.4 are important in determining catalytic efficiency and the protein processing of CYP1B1 in both COS-1 and other cellular expression systems. Recently, others have shown that the CYP1B1.4 variant increases the degradation efficiency of CYP1B1 by proteases and the proteasome in COS-1 cells, although the precise mechanism to explain these results remains to be elucidated (50,113). When expressed by bacteria in an ex vivo assay, the CYP1B1.3 variant alone was found have the lowest catalytically efficiency toward estrogen 4-hydroxylation reactions and the lowest ratio of 4-OHE 2 :2-OHE 2 formation.…”
Section: Polymorphismsmentioning
confidence: 99%
“…RNA-PCR studies have shown that expression of CYP1B1 is equivalent in normal and tumor tissues, whereas immunohistochemical analysis and activity assays indicate that protein expression is increased in tumors (4,5,63,68). This could suggest that (a) a certain threshold of mRNA expression must be present before the protein can be expressed, (b) cell-specific post-transcriptional modifications must be present before protein expression is achieved, and (c) proteolytic degradation can modulate CYP1B1 protein levels (50,69). Thus, cell-specific CYP1B1 transcriptional activity must be assessed using immunologic and activity assays in conjunction with mRNA detection.…”
Section: Problems With Mrna Detectionmentioning
confidence: 99%
See 3 more Smart Citations